(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Knowledge of tuberculosis is very important for the patients. Objective: This study was aimed to assess and explore the knowledge of TB patients regarding their diseases in Quetta, Pakistan. Methodology: This questionnaire based, cross sectional analysis was conducted in Fatima Jinnah Chest Hospital, Quetta with in all TB patients. Knowledge was assessed by using a pre-validated self-administered questionnaire containing 22 disease related questions. Convenience sampling technique was used for data collection. Descriptive analysis was used to demonstrate the characteristics of the study population. Result: Mean age of respondents was 40.99±18.10. Study was dominated by 168 (60.00%) of females. Two hundred (71.40%) were married. One hundred sixteen (41.40%) had no any education. One hundred sixty-eight (60.00%) were Pashtun. One hundred thirty-two (47.10%) having income less than 10000 PKR and ranges between 10000 to 18000 PKR respectively. One hundred fifty-six (55.70%) were having rural residency. One hundred fifty-six (58.10%) having no any co-morbidity. Mean score of knowledge was 11.23±3.616. Conclusion: Knowledge is a key factor in understanding any particular disease. If the level of knowledge is low in some or all parts of the disease, it will actually affect the patient. It can be concluded that there is a need to raise awareness of TB symptoms, mode of transmission, prevention, diagnosis and treatment of the disease through health education. Bangladesh Journal of Infectious Diseases 2020;7(2):78-83